Body Mass Index mediates the associations between dietary approaches to stop hypertension and obstructive sleep apnea among U.S. adults - Li, Songtao; Yang, Yuxin; Lin, Mengying; Lv, Tian; Pan, Yourang; Zhou, Jie (Frontiers in Nutrition, 2024)
BackgroundThe Dietary Approaches to Stop Hypertension (DASH) are associated with reduced cardiovascular, diabetes risk, but the effect on obstructive sleep apnea (OSA) is uncertain.MethodsThis study used data from the National Health and Nutrition Examination Survey (NHANES). DASH score was assessed through 24-h dietary recall interviews, and OSA diagnosis in individuals was based on predefined criteria. Logistic regression analysis was used to assess the association between DASH and OSA. Restricted cubic spline (RCS) analysis was used to investigate the dose–response relationship between DASH score and OSA risk. And comprehensive subgroup and mediation analyses were performed.ResultsAmong the 14,978 participants, 27.01% had OSA. DASH scores had a negative association with the risk of OSA (OR = 0.91, 95%CI: 0.88–0.95, p < 0.01). Next, we divided DASH scores into quintiles groups. In comparison to the reference group Q1, groups Q5 had adjusted OR values of 0.63 (95%CI: 0.52–0.76, p < 0.01). Subgroup analyses revealed that this association was consistent across different groups. Further mediation analyses showed that the associations of DASH with OSA risk parallelly mediated by the above Body Mass Index (BMI) 33.4%,95%CI (20.6–46.2%) (all p < 0.05). The restricted cubic spline (RCS) analysis indicated a significant dose–response relationship between DASH diet and OSA risk.ConclusionThese findings suggested that DASH decreased OSA risk, which was possibly and partly mediated by BMI.